1999
DOI: 10.1046/j.1365-2664.1999.00450.x
|View full text |Cite
|
Sign up to set email alerts
|

Successional response of a tropical forest termite assemblage to experimental habitat perturbation

Abstract: Summary 1.Research into the successional responses of tropical forest communities following disturbance has potential applications for habitat restoration. Currently little is known of how these responses relate to the recovery of biodiversity and ecosystem processes. Succession of assemblages of decomposer arthropods is essential for the recovery of the soil community and nutrient cycling processes. 2. This study investigated the successional response of a termite assemblage to the experimental perturbation o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
45
0
6

Year Published

2006
2006
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(52 citation statements)
references
References 30 publications
1
45
0
6
Order By: Relevance
“…Many studies have found that the short-term impact on the invertebrate community is imperceptible if the intensity of extraction is low as in our recently logged sites (Davies et al, 1999;termites, Siira-Pietikäinen et al, 2001;macroarthropods). Furthermore, some studies have not found a short-term effect, even after clear-cutting, on the macroinvertebrate community (Theenhaus and Schaefer, 1995).…”
Section: Macroinvertebrate Communities After Logging and Through Succmentioning
confidence: 93%
See 1 more Smart Citation
“…Many studies have found that the short-term impact on the invertebrate community is imperceptible if the intensity of extraction is low as in our recently logged sites (Davies et al, 1999;termites, Siira-Pietikäinen et al, 2001;macroarthropods). Furthermore, some studies have not found a short-term effect, even after clear-cutting, on the macroinvertebrate community (Theenhaus and Schaefer, 1995).…”
Section: Macroinvertebrate Communities After Logging and Through Succmentioning
confidence: 93%
“…It has been widely recognised that forest disturbance can affect nutrient cycling (Nilsson et al, 1995;Finér et al, 2003) and soil biota (Davies et al, 1999;Lavelle, 2000;Brown et al, 2001;Pietikäinen et al, 2003). Logging disturbance can have short-and long-term impacts on the below-ground subsystem.…”
Section: Introductionmentioning
confidence: 97%
“…A relatively large corpus of data is available on termite mound densities in natural and man-modified environments (Davies et al, 1999;Lepage and Darlington, 2000;Korb and Linsenmair, 2001), but fewer studies exist on the impact of management practices on termites (Davies, 1997;Eggleton et al, 1995), as outlined by Black and Okwakol (1997).…”
Section: Introductionmentioning
confidence: 99%
“…Negative distances from the wetland edge (located at 0 m) are inside the undisturbed wetland recover to a pre-disturbance state following restoration of degraded habitats (for a review, see Hoffman and . However, there is less known about the rate of recovery of community composition or relative abundance of species (Davies et al 1999). Despite the theoretical and practical importance of differential species losses for the stability of interactions in fragmented landscapes (Fagan et al 1999), to our knowledge no studies have monitored the strength of insect-plant interactions following habitat loss or tested whether these relationships can recover to a pre-disturbance state with restoration management.…”
Section: Discussionmentioning
confidence: 98%
“…Although restoration practices are widespread and sometimes large in scale, only a few studies have monitored changes in both plant and animal communities following habitat disturbance, as well as subsequently testing whether species assemblages recover following restoration (Davies et al 1999;Baer et al 2002). For example, Wassenaar et al (2005) monitored species assemblages of dung beetles, millipedes, trees, small mammals and birds in coastal dune forests after the removal of vegetation for mining.…”
Section: Introductionmentioning
confidence: 99%